The Influence of Board of Directors Characteristics on Financial Distress (Case Study of Automotive and Components Companies Listed on the IDX for 2017-2023) - Ningtyas Mardita Wulandari; Romli Romli (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This research is motivated by the delisting of automotive and component companies on the Indonesia Stock Exchange (IDX) in 2024. This issue can be explained by a variety of variables, such as the board of directors' approach to strategic decision-making.  As a result, the purpose of this study is to analyze and investigate the impact of board of directors characteristics, such as board gender diversity, board size, and board educational background, on financial distress in automotive and components companies listed on the IDX between 2017 and 2023.  The methodology used was a quantitative methodology with secondary data gathered from 11 companies' annual reports and financial statements over a seven-year observation period, yielding 77 samples obtained through a purposive sampling method. The financial distress variable is measured using the Altman Z-Score method. Data analysis is conducted using multiple linear regression with SPSS 31 software. The results of the partial analysis indicate that board gender diversity had a significant positive effect on financial distress, while board size had a significant negative effect. In contrast, board educational background was not found to have a significant effect. However, the simultaneous analysis revealed that the three board characteristics together had a significant impact on financial distress. These findings underscore the complexity of the board of directors' role in mitigating a company's financial risk, where the combination of these characteristics has a stronger effect than their individual influences.